Strengthening the Legislative Supervisory Function in the Provision of Human Resources in Era 5.0 Perspective of Fiqh Siyasah - ., Zuhraini; Mu'in, Fathul (KnE Social Sciences, 2024)
Indonesia is a country that adheres to a democratic system, the administration of its government in regencies and cities is autonomous whose formation is determined by the laws. The functions of the legislative body, in this case, the Regency / City DPRP based on Article 149 of Law Number 9 of 2015 concerning the second amendment to Law Number 23 of 2014 concerning Regional Government, including the functions of forming local regulations, budgeting, and supervision. In terms of supervision, it includes the provision of era 5.0 human resources. This research includes library research whose data sources are from laws and regulations and scientific articles. This research concludes that the role of legislative supervision needs to be optimized and strengthened in the era of Society 5.0. DPRD must maximize the supervision of local governments to prepare human resources that implement the use of technology to solve various service problems of the bureaucratic apparatus. This is in line with the concept of fiqh siyasah called Ahl-Al-Hall Wa-Aqd, which the people have trusted to represent them to oversee the running of the government properly. Keywords: supervision, legislative, human resources, Fiqh Siyasah